Correlation of SARS-CoV-2 IgG/IgM Levels to COVID-19 Severity in Convalescent Plasma Donor Candidates - Ratna Delima Hutapea; Rachmawati A. Muhiddin; Asvin Nurulita; Mansyur Arif; Kery Bayu Santoso Katjong (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Coronavirus Disease-19 (COVID-19) is an infectious disease caused by Sars-CoV-2. The clinical manifestations of COVID-19 vary from asymptomatic, mild symptoms to severe symptoms. Plasma of people recovering from COVID-19 infection will likely contain specific polyclonal antibodies. These antibodies can provide passive immunity to the recipient. This study aimed to analyze the correlation of SARS-CoV-2 IgG/IgM levels to COVID-19 severity and length of negative conversion in COVID-19 patients as convalescent plasma donor candidates. The retrospective research used this study with data collected from May to December 2020. The study sample of 30 patients was taken from the medical record with a population that met the inclusion criteria. IgG/IgM levels were measured using AFIAS-6 Immunoanalyzer. The Shapiro-Wilk and Spearman rho non-parametric correlation tests were used for data analysis. The statistical test results with p-value <0.05 were reported as significant. There was no significant correlation between IgM levels and COVID-19 severity, with a p-value of 0.763 (p>0.05) and length of negative conversion with a p-value of 0.998 (p>0.05). There was a significant correlation between IgG levels and COVID-19 severity with a p-value of 0.014 (p<0.05) and length of negative conversion with a p-value of 0.004 (p<0.05). IgM/IgG levels affect the severity of the disease. IgM levels increase at the beginning of infection and decrease as the disease progresses, and IgG levels will increase slowly. IgM levels cannot be used to detect previous SARS CoV-2 infection, whereas IgG levels affect the length of negative conversion. There was a significant correlation between IgG and the severity of COVID-19 with a correlation strength of R=0.444 (weak correlation) and with a length of negative conversion with a relationship strength of R=0.509 (moderate correlation). SARS CoV-2 IgG levels of convalescent plasma donor candidates correlated to the severity and length of negative conversion.